Two Cases of Sinonasal Non-Intestinal-Type Adenocarcinoma with Squamoid Morules Expressing Nuclear β-Catenin and CDX2: A Curious Morphologic Finding Supported by Molecular Analysis - Tatiana M. Villatoro; Stacey K. Mardekian (Case Reports in Pathology)
Sinonasal non-intestinal-type adenocarcinoma (non-ITAC) is a rare, morphologically diverse neoplasm of the head and neck. Squamoid morular metaplasia has recently been reported as an occasional finding in non-ITAC. Interestingly, these squamoid morules often show aberrant expression of CDX2 as well as nuclear expression of β-catenin, similar to other tumors that show this type of metaplasia, but the underlying mechanism responsible for this finding is not completely understood. We present two cases of low-grade non-ITAC with squamoid morules coexpressing CDX2 and nuclear β-catenin by immunohistochemistry, both of which were found to harbor a mutation in CTNNB1, the gene encoding β-catenin. This finding provides support that an alteration in the β-catenin pathway, including mutations in the β-catenin gene itself, is responsible for this recently described morphologic phenomenon in non-ITAC.